Analisis Penyusunan Capaian Pembelajaran Matematika Kurikulum Merdeka di SDS Trisula Perwari - Sahrun Nisa; Mai Sri Lena; Ghita Hasna Thayyiba; Intan Dwi Puspita (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
SDS Trisula Perwari Kota Bukittinggi is an educational institution that already uses the Merdeka Curriculum. With the implementation of the Merdeka curriculum, changes are expected, especially in learning mathematics. The purpose of this study was to analyze the preparation of Merdeka curriculum learning outcomes in mathematics learning at SDS Trisula Perwari Kota Bukittinggi. This research uses a qualitative descriptive method. The informants of this research were selected using purposive techniques and the subjects were the Head of SDS Trisula Perwari, the Curriculum Section of SDS Trisula Perwari and the Mathematics Teacher of SDS Trisula Perwari. Data collection was done through interviews and documentation methods. The data analysis method is interactive analysis method. The results showed that the learning outcomes of phase A, B and C of the Merdeka Curriculum Mathematics of SDS Trisula Perwari Bukittinggi were structured and well implemented. However, there are still obstacles to implementing an Merdeka curriculum. Therefore, the preparation and planning of the mathematics learning outcomes of SDS Trisula Perwari should be more carefully prepared so that the obstacles that arise can be avoided.